A note on the morphology of Telosma cordata (Burm. F.) Merr (Asclepiadaceae) / H. Sarina, M. Muzamil and I. Rosmahaiza - H., Sarina; Muzamil, M.; I., Rosmahaiza (2004)
Telosma cordata (Burm. F.) Merr. or Tongkin flower is a climber belonging to Asclepiadaceae. The morphology of the leaves and flowers were discussed in details. The species have a slender with cordate, thin leaves. The flowers are borne axially in cluster of two to 15. It is greenish during opening and later change to yellow-orange in colour. Observations on the ontogeny of the pistil, stamens, and corona reveals a pistil composed of two carpels with numerous ovules on a submarginal placenta, anthers with two locules, and twin pollinia. The corona originates as two vertically arranged protuberances on the dorsal surface of the filaments and develops rapidly during the late stages of floral ontogeny. T. cordata has great potential in lanscaping because of their strong fragrance at night.